2021
DOI: 10.1109/tuffc.2020.2988361
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Ferroelectricity and Multiferroicity in Binary Oxide Thin Films

Abstract: The observation of ferroelectric, ferromagnetic and ferroelastic phases in thin films of binary oxides attract the broad interest of scientists and engineers. However, the theoretical consideration of observed behaviour physical nature was performed mainly for HfO2 thin films from the first principles, and in the framework of Landau-Ginzburg-Devonshire (LGD) phenomenological approach with a special attention to the role of oxygen vacancies in both cases. Allowing for generality of the LGD theory we applied it … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The values of the elastic constants and electrostriction coefficients used for the phase field simulations are C 11 = 400.92 GPa, C 12 = 127.10 GPa, C 13 = 133.00 GPa, C 22 = 397.30 GPa, C 23 = 99.30 GPa, C 33 = 353.30 GPa, C 44 = 91.66 GPa, C 55 = 84.17 GPa, C 66 = 127.67 GPa, Q 13 = −0.02 m 4 C −2 , Q 23 = −0.015 m 4 C −2 , and Q 33 = −0.030 m 4 C −2 . Note that, in this work, due to the lack of proper experimental/first-principles based statistics, we assume the electrostrictive coefficients in a similar manner described by Glinchuk et al 63…”
Section: Resultsmentioning
confidence: 99%
“…The values of the elastic constants and electrostriction coefficients used for the phase field simulations are C 11 = 400.92 GPa, C 12 = 127.10 GPa, C 13 = 133.00 GPa, C 22 = 397.30 GPa, C 23 = 99.30 GPa, C 33 = 353.30 GPa, C 44 = 91.66 GPa, C 55 = 84.17 GPa, C 66 = 127.67 GPa, Q 13 = −0.02 m 4 C −2 , Q 23 = −0.015 m 4 C −2 , and Q 33 = −0.030 m 4 C −2 . Note that, in this work, due to the lack of proper experimental/first-principles based statistics, we assume the electrostrictive coefficients in a similar manner described by Glinchuk et al 63…”
Section: Resultsmentioning
confidence: 99%
“…Doped-HfO 2 materials have three types of crystal structures, namely, monoclinic, tetragonal, and cubic structures. The phase transition can be achieved through several approaches, for example, application of mechanical stress, postdeposition annealing, and application of higher deposition pressure [26,27]. In 2011, Böscke et al discovered that the use of Si as a dopant could facilitate the formation of asymmetric orthorhombic-phased HfO 2 and hence the generation of ferroelectricity in the film [20].…”
Section: Emerging Ferroelectric Materialsmentioning
confidence: 99%
“…The fact that we have seen ferroelectricity only in the oxygen-deficient N-doped samples (as was shown by XPS measurements) comes as no surprise. Indeed, numerical calculations have shown that ferroelectricity in binary oxide thin films, and generally multiferroicity, is related to oxygen vacancies [43]. In this case, oxygen vacancies, as elastic dipoles, can be partially transformed into electric dipoles due to symmetry-breaking interfaces and defects (including grain boundaries in the case of polycrystalline samples), around which vacancies tend to accumulate by diffusing through the sample.…”
Section: Electrical Characterization Of Nio:n Samplesmentioning
confidence: 99%